Pelatihan Pembuatan Sabun Ecoenzyme untuk Meningkatkan Pendapatan Keluarga di Kelurahan Tegalsari Kota Tegal: Training on Eco-Enzyme Soap Making to Increase Family Income in Tegalsari Village, Tegal City - Oktaviani, Dian Nataria; Hendaryati, Neni; Herdiani, Renie Tri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
A training program on eco-enzyme soap making was conducted in July 2024 for 22 PKK members in Tegalsari Village, Tegal City. The program aimed to enhance the utilization of organic waste and equip participants with new skills. The training successfully improved participants' understanding of the eco-enzyme soap-making process, although some practical challenges were encountered. Evaluation results indicated that participants were enthusiastic and capable of producing bar soap. This initiative is expected to serve as a foundation for developing local-resource-based creative economies and promoting environmentally friendly behaviors.